Resilience processes in migrants: biographical narratives of Brazilians in Portugal - Roberto, S.; Moleiro, C. (Psicologia em Estudo, 2015)
Studies on migration have focused on the difficulties, barriers and obstacles upon arrival and stay in the host country. Recognizing the existence of these adverse processes, just a few studies have been turning their attention to the way that migrants overcome the difficulties they encounter. Moreover, a small number of studies have been investigating the migration process as a whole, starting in the country of origin. Based on the resilience theoretical perspective, this study sought to understand the adversity contexts and the resources mobilized by Brazilian migrants in Portugal, throughout their life trajectories, observed on the link between the country of origin and the host country, through 12 biographical narratives. The analysis of the narratives revealed the diversity of resilience processes amongst those migrants. It revealed that the adverse context arose by means of devaluation and rejection relationships with the Portuguese, stressing the importance of affective ties, sense of belonging, as well as the role of the Brazilian diaspora in Portugal, as meaningful resources. The article also discusses the clinical implications of the analysis of the narratives, from a resilience perspective.